Prevention of corneal allograft rejection in a mouse model of high risk recipients - Vítová, A; Filipec, M; Zajícová, A; Krulová, M; Holán, V (The British journal of ophthalmology, 2004)
AIM: To determine the effectiveness of treatment with immunosuppressive drugs and monoclonal antibodies (mAb) after penetrating keratoplasty in two different models of high risk mouse recipients. METHODS: Corneas were grafted orthotopically in mouse models of high risk recipients with either neovascularisation of the graft bed or presensitisation to graft donor antigens. Recipients were treated with mAb against CD4(+) or CD8(+) cells or against T cells, or were treated with cyclosporin A (CsA) or mycophenolate mofetil (MMF), or a combination of both drugs. RESULTS: Control untreated recipients with neovascularised graft bed or presensitised to the graft donor antigens rejected corneal allografts in 12.5 (SD 2.3) and 9.9 (1.6) days, respectively. Treatment of graft recipients with a neovascularised graft bed with mAb anti-CD4 or anti-T cells, but not with mAb anti-CD8 or with immunosuppressive drugs, resulted in a significant prolongation of graft survival; 75% and 28.5%, respectively, of grafts survived for more than 45 days after grafting. However, none of the treatments were successful in presensitised recipients. CONCLUSIONS: Treatment of high risk recipients with mAb anti-CD4 is more effective in preventing corneal allograft rejection than the treatment with mAb anti-CD8 or the immunosuppressive drugs MMF and CsA. However, the effectiveness of the treatment depends on the recipients' pretransplantation risk type.
Keywords: keratoplastika perforující; Keratoplasty, Penetrating; Graft Rejection; Antibodies, Monoclonal; Female; přežívání štěpu; Mycophenolic Acid; myši inbrední BALB C; zvířata; myši; myši inbrední C57BL; imunosupresiva; imunosupresivní léčba; CD8-Positive T-Lymphocytes; Mice; Mice, Inbred BALB C; CD8-pozitivní T-lymfocyty; Immunosuppressive Agents; Postoperative Care; cyklosporin; ženské pohlaví; CD4-Positive T-Lymphocytes; Male; pooperační péče; Mice, Inbred C57BL; Immunosuppression Therapy; kyselina mykofenolová; monoklonální protilátky; CD4-pozitivní T-lymfocyty; Cyclosporine; Animals; mužské pohlaví; Graft Survival; Disease Models, Animal; rejekce štěpu; modely nemocí na zvířatech